Literasi Digital Siswa : Studi Deskriptif pada Pembelajaran Biologi di SMA - Ananda, Oriny Tri; Mahanal, Susriyati; Susanto, Hendra (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Understanding of complex biology material requires students' ability to select, process, interpret, and evaluate information from various sources on the internet, so that digital literacy is needed by students. This study aims to find out how students' digital literacy abilities are in biology learning at school. This research is quantitative descriptive. The population in this study were all students of SMA Negeri 11 Makassar, while the research sample consisted of 105 students selected by random sampling. The research instrument used was a student digital literacy questionnaire consisting of 24 statement items with five answer choices, namely strongly disagree (STS), disagree (TS), have no opinion (TB), agree (S), and strongly agree (SS). Data was collected by distributing questionnaires to students using Google Forms. The data obtained was analyzed using descriptive analysis by making percentages which were then interpreted based on the percentage categories of students' digital literacy scores. The research results show the percentage of each student digital literacy indicator, namely the finds indicator is 42,54% in the medium category, the use multiple sources indicator is 40,95% in the medium category, the selects indicator is 36,76% in the low category, the evaluates indicator is 35% in the low category, the considers source, message effect indicator is 34,7% in the low category, and the uses to produce original work indicator is 36,1% in the low category. The average percentage of students' digital literacy for all indicators is 37,68%, which shows that students' digital literacy in biology learning is in the low category.